Islamic Character Education in the Digital Era: A Systematic Literature Review of Challenges, Strategies, and Learning Innovations - Affan Haydar; Benny Prasetiya (PT. Education Research Center, 2026)
The development of digital technology has influenced nearly every aspect of life, including Islamic education and the character formation of students. The emergence of social media, digital platforms, and the highly open flow of information has brought positive impacts, such as easier access to knowledge. However, it has also given rise to various moral issues, including cyberbullying, the spread of misinformation (hoaxes), hate speech, and the decline of communication ethics in digital spaces. This situation requires Islamic education to adopt more adaptive approaches so that religious values can continue to be effectively internalised among the younger generation. This study aims to examine the challenges of Islamic character education in the digital era, analyse strategies that can be implemented, and identify learning innovations that are relevant to modern technological developments. The research employs a qualitative approach using a Systematic Literature Review (SLR) method through the collection, selection, and analysis of various scholarly works related to Islamic character education and the digitalisation of education. The findings indicate that Islamic character education requires the integration of religious value reinforcement and digital literacy to enable students to use technology wisely, critically, and responsibly. Furthermore, the use of interactive learning media, blended learning approaches, and educational social media platforms is considered effective in enhancing the internalisation of moral and spiritual values. Therefore, Islamic character education plays a crucial role in shaping a generation that is not only technologically competent but also possesses moral integrity, spiritual awareness, and social responsibility amid the ongoing development of digital society.